Guidance Note on Letters and Statements Assessing Members' Economic Conditions and Policies. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2018)
This note provides guidance on assessment letters and statements, including identifying the circumstances in which they are called for, and outlining the content, the review process, and the ground rules for circulation to the Board and for publication. Such letters or statements may be prepared for countries with programs supported by the Fund through financial assistance, a Policy Support Instrument (PSI) or Policy Coordination Instrument (PCI), countries receiving Fund emergency assistance, countries with staff-monitored programs (SMPs), or surveillance-only cases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Assessment Letters; Assessment; Letter; Policy; PP